Nick-seq for single-nucleotide resolution genomic maps of DNA modifications and damage. Issue 12 (2nd June 2020) - Cao, Bo; Wu, Xiaolin; Zhou, Jieliang; Wu, Hang; Liu, Lili; Zhang, Qinghua; DeMott, Michael S; Gu, Chen; Wang, Lianrong; You, Delin; Dedon, Peter C
Abstract: DNA damage and epigenetic marks are well established to have profound influences on genome stability and cell phenotype, yet there are few technologies to obtain high-resolution genomic maps of the many types of chemical modifications of DNA. Here we present Nick-seq for quantitative, sensitive, and accurate mapping of DNA modifications at single-nucleotide resolution across genomes. Pre-existing breaks are first blocked and DNA modifications are then converted enzymatically or chemically to strand-breaks for both 3′-extension by nick-translation to produce nuclease-resistant oligonucleotides and 3′-terminal transferase tailing. Following library preparation and next generation sequencing, the complementary datasets are mined with a custom workflow to increase sensitivity, specificity and accuracy of the map. The utility of Nick-seq is demonstrated with genomic maps of site-specific endonuclease strand-breaks in purified DNA from Eschericia coli, phosphorothioate epigenetics in Salmonella enterica Cerro 87, and oxidation-induced abasic sites in DNA from E. coli treated with a sublethal dose of hydrogen peroxide. Nick-seq applicability is demonstrated with strategies for >25 types of DNA modification and damage.